HORTICULTURAL RESEARCH AND DEVELOPMENT CENTER IN SEMARANG REGENCY: INTEGRATING ECOLOGICAL ARCHITECTURE - Ismi Nabilla, Anggia (Jurnal Poster Pirata Syandana, 2024)
Indonesia, with its abundant natural resources and tropical climate, is renowned as an agrarian nation where the agricultural sector plays a vital role in social, economic, and trade advancements. In Kabupaten Semarang, a district exemplifying specialized agriculture, particularly horticulture, stands as a pivotal economic contributor, comprising 20.71% of the total Gross Regional Domestic Product (GRDP) in 2021. The cultivation of annual and seasonal horticultural crops is particularly promising, with significant contributions of 5.61% and 2.68%, respectively, driven by favorable climatic and land conditions. Especially, highland vegetable crops in this region thrive due to these conducive factors. However, the absence of integrated research and development facilities hampers the potential of this sector. The establishment of such infrastructure is crucial to enhancing agricultural competitiveness, labor absorption, farmer income, regional economies, and national revenue. Furthermore, in the context of the Fourth Industrial Revolution, adopting ecological architecture principles in horticultural development aligns with the synergy between humanity and the environment, ensuring sustainability and harmony between human activities and natural ecosystems.